Internationalization, competition and transfer of knowledge - and the efforts by companies in BRIC countries to enter markets in USA and Europe - Westeren, Knut Ingar (Informe GEPEC, 2014)
Internationalization and competition now cuts across national borders, a firm’s position in one country is no longer independent from its position in other countries. This has at least two implications, it is an advantage for the firm to be present in several major growth markets. It is also desirable integrate its activities on a worldwide scale, in order to exploit and coordinate linkages between these different locations. Competition also cuts across sector boundaries and market segments: This growing complexity of competition has changed the determinants of firm organization and growth, as well as the determinants of location. No firm, not even a dominant market leader, can generate all the different capabilities internally that are necessary to cope with the requirements of global competition. In this paper we will use the Brazilian company JBS’ acquisition of the US company Pilgrim’s Pride at the end of 2009 as an example to look further into the questions raised above.